A review on ultrasonic alchemy of oil-based nanofluids for cutting-edge dielectric and heat transfer oils - Farade, Rizwan A.; Abdul Wahab, Noor Izzri; Mansour, Diaa-Eldin A.; Junaidi, Nusrath; Soudagar, Manzoore Elahi M.; Rajamony, Reji Kumar; AlZubaidi, A. (Elsevier, 2024)
Oil-based nanofluids can significantly improve dielectric and thermal performance across various applications. The dispersion dynamics of oil-based nanofluids rely on the intricate interplay of diverse microscopic forces acting upon the nanoparticles. Ultrasonication effectively manages these forces to improve nanoparticle dispersion stability. However, researchers are still captivated by the complex understanding of the underlying mechanisms and parameter correlations. Ultrasonication fosters dispersion stability by breaking up clusters of nanoparticles and exfoliating nanosheets. Additionally, understanding the significance of ultrasonication on the thermo-dielectric performance of oil-based nanofluids using empirical equations is crucial. This review delves into the understanding the intricate mechanism and its significant influence on the performance of oil-based nanofluids, with a focus on sustainability and efficiency. The novelty of this study lies in in-depth examination of cutting-edge literature. The oil matrices encompassed in this study are dielectric and heat transfer fluids. The nanofillers encompassed are carbon-based, compounds, metal oxides, non-carbon two-dimensional (2D) materials, hybrid, functionalized, and doped nanoparticles. Moreover, comprehensive table emphasises base oil and nanofiller type, concentration, size, sonication type and time, and key findings. This work provides important insights into the effects of ultrasonication on the performance of oil-based nanofluids, underlying mechanisms, parameter correlations, and equations. Therefore, this review is highly valuable for researchers and practitioners, offering great opportunities for improvement.